Análisis de los procesos que influyen en el Mercado Sostenible y Economía Circular (2022)
he results obtained in the present investigation allowed us to know the need to open an ecofriendly market for the commercialization of products in order to respond to the needs of consumers and the preservation of natural resources. The background, problems and concepts associated with the research topic and its relationship with individual and business responsibility in the face of environmental effects are presented in a framework of social and economic awareness. Subsequently, the objectives related to research on the need for a sustainable market were established, which are supported by the issues addressed in the theoretical framework, such as sustainability, sustainable development, environment, circular economy, eco-friendly markets, this with in order to address each of the factors associated with this type of project as a sustainable business model that responds to the urgent need for sustainable solutions that promote an improvement in consumption habits and delay the catastrophic consequences on the natural resources of the planet, which are constantly threatened by the overexploitation of companies and governments whose actions respond to consumer demand, ignoring the responsibility they must assume as regulatory entities Taking this into account, it is important to bring innovation and influence on purchasing habits through new proposals and methodological tools that allow the elimination of stigmas and paradigms present in the trade of second-hand products or that are within the classification of The rule of the 3 Rs: Reduce, Reuse and Recycle With clear concepts and the problem identified, we proceed to the development of the methodological framework that will not only allow the definition of the methodologies chosen for the research, but will also contain the tools that will allow optimal data collection, which will yield results that can be analyzed. with each other, that is, the qualitative information will complement the quantitative information to determine the degree of need for an eco-friendly market for the commercialization of sustainable products in the city of Santa Marta, Colombia